Comparing the Impact of Different Antiarrhythmic Classes on Clinical Outcomes Following Atrial Fibrillation Catheter Ablation - Andrej Belančić; Yusuf Ziya Sener; Metin Oksul; Cansu Ozturk; Serdar Soner; Adnan Duha Comert; Gamze Yeter Arslan; Dinko Vitezić; Bojan Jelaković; Erkan Baysal (Pharmaceuticals, 2025)
Background/Objectives: Catheter ablation has become the standard of care for patients with symptomatic and drug-refractory atrial fibrillation (AF). Both Class IC and Class III antiarrhythmic drugs (AADs) are effective in preventing early recurrences of AF, but not late recurrences, compared with the usual care. We aimed to compare the effects of two months of Class IC versus Class III AADs following AF catheter ablation on clinical outcomes, including arrhythmia recurrence and safety endpoints. Methods: All patients undergoing AF catheter ablation between January 2015 and November 2024 were screened, and cases meeting the inclusion criteria were included. Primary outcome was defined as atrial tachycardia recurrence-free survival. Results: A total of 98 patients (mean age 54.2 ± 14.0 years; 55.1% male) were enrolled, with 66.3% presenting with paroxysmal atrial fibrillation (AF). The mean left atrial diameter was 38.7 ± 5.1 mm, and 78.6% underwent cryoballoon ablation. Class IC AADs were administered to 62 cases, while the remaining 36 patients received amiodarone following catheter ablation. The rate of atrial tachycardia (ATa) recurrence was comparable between the patients treated with Class IC and Class III AADs (9.7% vs. 19.4%; p = 0.169). Predictors of ATa recurrence were identified as history of direct current cardioversion—DCCV (HR: 5.86; 95%CI: 1.44–23.82)—and LA diameter (HR: 1.17; 95%CI: 1.04–1.31). The most frequent AAD-related adverse event was symptomatic bradycardia (6.1%), which resolved in all cases following dose reduction. Conclusions: Class IC and Class III antiarrhythmics show comparable efficacy in terms of preventing ATa recurrence following AF catheter ablation. AAD-related adverse event rates are negligible for short-term use.